PENGEMBANGAN MANAJEMEN PEMBINAAN SANTRIWAN/SANTRIWATI TPQ NURUL FALAH NAGARI TALANG KOTO PULAI TAPAN KECAMATAN RANAH AMPEK HULU TAPAN - Ramadani, Suci Nofrisa; Daflaini, Daflaini; Meditamar, Muhd. Odha Meditamar (Institut Agama Islam Negeri Kerinci, 2022)
The aim of this research is to develop management for the development of Islamic boarding school students at TPQ Nurul Falah. This activity uses a qualitative method with a case study approach. A case study is a model that focuses on exploration or a particular case that is reviewed in detail and in depth in the form of how and why questions. The sample collection technique uses a non-random sampling method or known as Purposive Sampling, where the researcher ensures that the illustration is quoted through a method of determining a special identity that suits the research objectives so that it is hoped that they can respond to the research case. From the activities that have been carried out, the following conclusions can be drawn: 1) KKN students are required to be able to live in society and understand the reality of society by using the knowledge, attitudes and skills they have; 2) The KKN work programs, both group and individual, that are implemented are mostly able to run as they should, although there are adjustments in time to the conditions and situation of the community environment. The success of group and individual KKN programs will ultimately provide mutual benefits between the community and students. The positive impact for students is increasing awareness of the surrounding environment and broadening their horizons of thought. Meanwhile, for society, it is to increase the spirit of hard work, the desire to progress, a positive mental attitude, a critical mindset.